The effect of fine service on customer loyalty in rural homestays: The mediating role of customer emotion - Xing, Bo; Li, Shihan; Xie, Dingding (Frontiers in Psychology, 2022)
Rural homestay is an important carrier for developing rural tourism, which still grows against the wind in the post-epidemic era of COVID-19 virus and shows unique attributes that are different from those of the traditional hospitality industry. Based on the five-dimensional model of fine service theory, this study introduces culture as a unique dimension to construct a six-dimensional model of rural homestay fine service and explores the influence mechanism of rural homestay fine service on customer loyalty. This study successively used expert interviews and questionnaires to fit the structural equation model through SPSS 26.0 and AMOS 24.0, and the results showed that culture, as a unique attribute of rural homestay, is another important factor influencing the level of rural homestay fine service besides privacy, responsiveness, empathy, comfort, and psychological quality. Customer emotion of rural homestay significantly affects customer loyalty and fully mediates the relationship between fine service and customer loyalty. This study verifies the effectiveness of fine service theory in the research of rural homestay good service and provides a new measuring tool, which is also enriching and developing the exploration of fine service.